Stent extension into a single inflow vessel is a valuable option after endophlebectomy. (October 2018) - van Vuuren, Timme MAJ; Kurstjens, Ralph LM; de Wolf, Mark AF; van Laanen, Jorinde HH; Wittens, Cees HA; de Graaf, Rick
Background: Venous stenting with an endophlebectomy and arteriovenous fistula can be performed in patients with extensive post-thrombotic changes. However, these hybrid procedures can induce restenosis, sometimes requiring stent extension, into a single inflow vessel. This study investigates the effectiveness of stenting into a single inflow vessel. Methods: All evaluated patients had temporary balloon occlusion of the arteriovenous fistula to evaluate venous flow into the stents. When stent inflow was deemed insufficient, AVF closure was postponed and additional stenting was performed. Patency rates and clinical outcomes were evaluated. Results: Twenty-four (38%) of 64 patients had additional stenting. The primary, assisted primary and secondary patency were 60 %, 70% and 70% respectively. Villalta score reduced by 6.1 points ( p  < 0.001), and venous clinical severity score by 2.7 points ( p  = 0.034). Conclusion: Stenting through the femoral confluence into a single inflow vessel is a feasible bailout option if primary hybrid intervention fails with relative high patency rates and clinical improvement.